2020
DOI: 10.1108/emjb-08-2019-0101
|View full text |Cite
|
Sign up to set email alerts
|

Does currency misalignment matter for economic growth? – Evidence from Turkey

Abstract: PurposeThe study mainly aims to examine the currency misalignment of Turkish lira and evaluate if it has an impact on economic growth of Turkey.Design/methodology/approachIt relies on Johansen cointegration technique for measuring currency misalignment relying on single-equation approach and the autoregressive distributed lag (ARDL) approach to evaluate how misalignment affects economic growth. The sample period covers from 1980 to 2016.FindingsThe study identifies that terms of trade, relative productivity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The Granger causality showed the non-existence causality between the misalignments of the real exchange rate. The results are similar to some of the studies including Missio et al (2015) , Vieira & MacDonald (2012) and contrasting with (Dani Rodrik, 2009;Mamun et al, 2020;Tarawalie, 2011;Tarawalie, 2021;Tsen Wong, 2013).…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
See 1 more Smart Citation
“…The Granger causality showed the non-existence causality between the misalignments of the real exchange rate. The results are similar to some of the studies including Missio et al (2015) , Vieira & MacDonald (2012) and contrasting with (Dani Rodrik, 2009;Mamun et al, 2020;Tarawalie, 2011;Tarawalie, 2021;Tsen Wong, 2013).…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
“…The study found the significant impact of misalignment episodes on economic growth. Mamun et al (2020) explored the effect of real exchange rate misalignment using a single equation approach for Turkey for the period of 1980 to 2016 using the ARDL approach. The results were similar to Dani Rodrik (2009) that is higher the undervalued real exchange rate, the higher the growth with linear relation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some recent studies supported neither Rodrik's (2008) nor WCviews. In contrary to the conventional theory, undervaluation falters economic growth of Turkey, while overvaluation promotes it ( Mamun et al., 2021 ). The RER misalignment may have two partially conflicting goals where undervaluation helps output growth by stimulating technological progress and knowledge spillovers, but it harms growth by raising income inequality.…”
Section: Empirical Reviewsmentioning
confidence: 94%
“…LDC economies might benefit from increased real investment and net foreign assets development, but this could be offset by a drop-in growth if RER misalignment, trade liberalization, and government development aid increase CO 2 emissions. Currency misalignment has been shown to hurt financial growth through the ARDL technique (Mamun et al, 2020). With an overvalued RER, LDCs' external competitiveness and financial performance might be improved by effective exchange rate management and consistent macroeconomic policy implementation that impact CO 2 emissions.…”
Section: Estimation Of Real Exchange Rate Misalignmentmentioning
confidence: 99%